الصادرات والصادرات خارج قطاع المحروقات احصائيات ومؤشرات للفترة 2000-2021 - جواهرة صليحة; ششوي حسنى (جامعة الوادي University of Eloued, 2024)
الهدف من هذه الدراسة هو تقديم تحليل شامل لقطاع الصادرات والصادرات خارج قطاع المحروقات في الجزائر خلال الفترة من 2000 -2021، بهدف فهم أهم الجوانب المؤثرة في هذا القطاع والتحديات التي يواجهها. وقد أظهرت الدراسة أن الاقتصاد الجزائري ما زال يعتمد شكل كبير على صادرات النفط والغاز، حيث تمثل هذه الصادرات نسبة كبيرة من الايرادات النقدية للبلاد. وبالرغم من جهود الحكومة في تنويع قاعدة الصادرات وتحفيز الصادرات غير النفطية، إلا أن التقدم في هذا المجال كان بطيئا. وتتمثل التحديات التي تواجه الصادرات غير النفطية في الجزائر في قلة التنويع في المنتجات المصدرة، وضعف التكنولوجيا والبنية التحتية، بالإضافة إلى القيود التجارية والمشاكل اللوجستية. مقابل هذه التحديات، لا يخفى علينا أن هناك فرصا كبيرة لتطوير قطاع الصادرات غير النفطية في الجزائر مثل استثمارات في قطاع الزراعة والصناعة والخدمات. The aimofthisstudyistoprovide a comprehensiveanalysisofthe non-oilexportssector in Algeriafrom 2000 to 2021, aimingtounderstandthekeyfactotsinfluencingthissector and thechallengesitfaces. The study has shown that the Algerian economy still heavily relies on oil and gas exports, which constitute a significant portio of the cuontry’s cash revenues. Despite the government’s efforts to diversify the export base and promote non-oil exports, progress in this area has been slow. Challenges facing non-oil exports in Algeria include limites product diversification, as well as trade restrictions and logistical issues. In the face of these challenges, it is clear to us that there are significant opportunities for developing the non-oil exports sector in Algeria, such as investments in the agriculture, industry, and services sectors.
Exports and exports outside the hydrocarbon sector in Algeria: Statistics and indicators for the period 2000 - 2021
Keywords: التجارة الخارجية; الميزان التجاري; الصادرات; الصادرات غير النفطية